2016
DOI: 10.1159/000452148
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Tattoo Complications in a Hospital Material of 493 Adverse Events

Abstract: Background/Aims: Tattooing is a global trend. Clinical knowledge of complications is based on case reports collected over a century. Larger cohorts reflecting complications associated with contemporary trends are lacking. Methods: The study was a retrospective review of a consecutive cohort of patients with tattoo complications diagnosed in the “Tattoo Clinic“ of Bispebjerg University Hospital in Copenhagen, Denmark, from 2008 to 2015, based on patient history and systematic clinical examination. Results: A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
133
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 91 publications
(142 citation statements)
references
References 35 publications
7
133
0
2
Order By: Relevance
“…Unbearable itch or pain was a reason for requesting tattoo removal. Red ink was the main culprit, but the actual allergens have not yet been identified [24,26] . It is widely acknowledged that patch-testing is not suitable for exploring tattoo allergies [24,27] and therefore we rarely use this test for tattoo reactions in our practice.…”
Section: Tattoo Allergy Is the Most Common Complication And Occurs Onmentioning
confidence: 99%
“…Unbearable itch or pain was a reason for requesting tattoo removal. Red ink was the main culprit, but the actual allergens have not yet been identified [24,26] . It is widely acknowledged that patch-testing is not suitable for exploring tattoo allergies [24,27] and therefore we rarely use this test for tattoo reactions in our practice.…”
Section: Tattoo Allergy Is the Most Common Complication And Occurs Onmentioning
confidence: 99%
“…In our initial publication, "Classification of Tattoo Complications in a Hospital Material of 493 Adverse Events," we observed that black pigment and a papulonodular type of tattoo reaction by clinical examination are associated [11] . Sarcoid granulomas are clinically and by shape nodular.…”
mentioning
confidence: 99%
“…Mutagenic or reproduction-toxic events directly in humans have neither been reported. A large consecutive series of 405 patients with tattoo complications, published from our clinic, found no cases of malignant tumours in the skin or in the internal organs [18] . Old studies with 25-year follow-up from the Mayo Clinic in USA on extensive tar treatment of atopic dermatitis and psoriasis, supplemented with UVR given as Goeckerman therapy, failed to show increased risk of cancers in the skin and in internal organs [19][20][21] .…”
Section: Discussionmentioning
confidence: 88%